Biorreator anaeróbio de membrana submersa aplicado ao tratamento de esgoto doméstico - Targino, Ana Paula de Melo (2024)
Domestic sewage is often released into the environment without proper treatment, causing contamination of soil and water, as it contains contaminants such as N and P. The submerged membrane anaerobic bioreactor could be an advanced treatment alternative to help remove these contaminating compounds in domestic sewage. The objective of the study was to evaluate the feasibility of applying a submerged membrane anaerobic bioreactor for the treatment of domestic sewage aiming to remove organic matter and nutrients such as nitrogen and phosphorus. The sewage used was of domestic origin, collected from the UFPB student's home and from the Paraíba sewage treatment plant. The evaluation was carried out from March 2023 to February 2024. The parameters evaluated were: COD, BOD, N, P, Turbidity and pH. The equipment used for evaluation was: UV pastel, spectrophotometer, turbidimeter and pH meter, respectively. From the results obtained, the efficiency was calculated, where COD, BOD, N and P and turbidity were removed. The sewage treatment system composed of a submerged membrane anaerobic bioreactor showed a removal efficiency of 70% for COD and BOD, 12% for N, 16% for P and 62% for Turbidity. It is recommended, as future studies, to keep the system at a temperature of 35°C to analyze the amount of biogas generated, as well as the use of residual sludge from the system as organic fertilizer and a source of Nitrogen and Phosphorus for plants.